2003
DOI: 10.1086/374383
|View full text |Cite
|
Sign up to set email alerts
|

Significant Linkage of Parkinson Disease to Chromosome 2q36-37

Abstract: Parkinson disease (PD) is the second most common neurodegenerative disorder, surpassed in frequency only by Alzheimer disease. Elsewhere we have reported linkage to chromosome 2q in a sample of sibling pairs with PD. We have now expanded our sample to include 150 families meeting our strictest diagnostic definition of verified PD. To further delineate the chromosome 2q linkage, we have performed analyses using only those pedigrees with the strongest family history of PD. Linkage analyses in this subset of 65 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(69 citation statements)
references
References 19 publications
1
67
0
1
Order By: Relevance
“…These mutations may account for PD in as many as 50% of familial cases of autosomal recessive juvenile parkinsonism [45,46]. Clinically, the disease usually begins when the patient is in his/her 20s, and is prominently associated with dystonia and diurnal fluctuations, progressing slowly while accompanied by early and severe levodopa-induced dyskinesis, but no dementia.…”
Section: Parkin Genementioning
confidence: 99%
“…These mutations may account for PD in as many as 50% of familial cases of autosomal recessive juvenile parkinsonism [45,46]. Clinically, the disease usually begins when the patient is in his/her 20s, and is prominently associated with dystonia and diurnal fluctuations, progressing slowly while accompanied by early and severe levodopa-induced dyskinesis, but no dementia.…”
Section: Parkin Genementioning
confidence: 99%
“…The products of these genes are alpha-synuclein (SNCA), parkin (ubiquitin-conjugating enzyme; UBCH7; PARK2), ubiquitin Cterminal hydrolase L1 (UCHL1), PTEN-induced kinase 1 (PINK), DJ-1 and leucine-rich repeat kinase 2 (LRRK2). Additional loci harbouring presumptive PD genes have been mapped including PARK3 [19], PARK10 [24] and PARK11 [51].…”
Section: Introductionmentioning
confidence: 99%
“…17 An additional study was performed using a subset of the previous, but expanded sample, which included only pedigrees with a strong family history of PD: in an analysis of 65 families (77 sibling pairs) a maximum LOD score of 5.1 at the marker D2S206 on chromosome 2q36-37 was found using an autosomal dominant model of disease transmission. 18 Recently, Pankratz et al 19 confirmed their previous results using a further enlarged sample of 85 families (113 sibling pairs) with a strong family history of PD: they again reported a linkage to the 2q36 -37 region (LOD score 4.9).…”
Section: Introductionmentioning
confidence: 69%
“…The inclusion of the families with parkin mutations resulted in a higher LOD score, but the LOD score remained clearly significant in the sample without parkin mutations. 18,19 We repeated our linkage analysis excluding nine families, in which we could not rule out linkage to marker D6S305 in the parkin gene. Excluding these families did not change our overall results, indicating that there is no specific contribution of this subset of families to our results.…”
Section: Discussionmentioning
confidence: 99%